Intrinsic Risk Factors for First-Time Noncontact ACL Injury: A Prospective Study of College and High School Athletes. (May 2023) - Beynnon, Bruce D.; Tourville, Timothy W.; Hollenbach, Helen C.; Shultz, Sandy; Vacek, Pamela
Background: A comprehensive understanding of the intrinsic risk factors for anterior cruciate ligament (ACL) disruption is important for identifying individuals at increased risk for suffering this trauma and developing interventions to mitigate risk. Hypothesis: A variety of risk factors predispose athletes to first-time, noncontact ACL injury and some of these differ between male and female athletes. Study Design: Prospective cohort study with nested case-control sampling. Level of Evidence: Level 2. Methods: Sport teams at 28 high schools and 8 colleges were monitored prospectively over 4 years, and 109 of 130 athletes who suffered their first noncontact ACL injury participated in the study. At the time of injury, matched control subjects were randomly selected from among the case's teammates and a total of 227 athletes participated. Demographic characteristics, joint laxity, lower extremity alignment, strength, and personality characteristics were measured. The association of each risk factor with injury risk was assessed by conditional logistic regression. Results: The risk factors that were associated with ACL injury in both male and female athletes included having a parent with prior ACL injury and increases of the following variables: body weight, anterior displacement of the tibia relative to the femur, genu recurvatum, and generalized joint laxity. Risk factors that are unique to female athletes included increased body mass index, increased trunk flexion strength, and prior non-ACL knee injury. The risk factors specific to male athletes were decreased standing quadriceps angle, decreased hip adduction strength, and chronic disease. Conclusion: A diverse set of risk factors predispose both male and female athletes to ACL injury, whereas others appear to be sex-specific. Clinical Relevance: Different approaches for assessing risk and preventing ACL injury are needed for male and female athletes. In addition, personalized prevention strategies may be needed to target the specific characteristics that place an individual at increased risk of suffering this trauma.